Subclinical Myocardial Disease in Heart Failure Detected by CMR - Ohyama, Yoshiaki (2014)
Noninvasive cardiac imaging plays a central role in the assessment of patients with heart failure at all stages of disease. Moreover, this role can be even more important for individuals with asymptomatic cardiac functional or structural abnormalities—subclinical myocardial disease — because they could have benefits from early interventions before the onset of clinical heart failure. In this sense, cardiac magnetic resonance offers not only precise global cardiac function and cardiac structure, but also more detailed regional function and tissue characterization by recent developing methods. In this section, some of the main methods available for subclinical myocardial disease detection are reviewed in terms of what they can provide and how they can improve heart failure assessment.